Genetic counselling and testing in pulmonary arterial hypertension: a consensus statement on behalf of the International Consortium for Genetic Studies in PAH - Eichstaedt, Christina; Belge, Catharina; Chung, Wendy K.; Gräf, Stefan; Grünig, Ekkehard; Montani, David; Quarck, Rozenn; Tenorio-Castano, Jair A.; Soubrier, Florent; Trembath, Richard C.; Morrell, Nicholas W. (The European respiratory journal, 2023)
Pulmonary arterial hypertension (PAH) is a rare disease that can be caused by (likely) pathogenic germline genomic variants. In addition to the most prevalent disease gene, BMPR2 (bone morphogenetic protein receptor 2), several genes, some belonging to distinct functional classes, are also now known to predispose to the development of PAH. As a consequence, specialist and non-specialist clinicians and healthcare professionals are increasingly faced with a range of questions regarding the need for, approaches to and benefits/risks of genetic testing for PAH patients and/or related family members. We provide a consensus-based approach to recommendations for genetic counselling and assessment of current best practice for disease gene testing. We provide a framework and the type of information to be provided to patients and relatives through the process of genetic counselling, and describe the presently known disease causal genes to be analysed. ...
Gesehen am 13.06.2023